Pandangan filsafat terhadap ilmu pedagogi olahraga - Hita, I Putu Agus Dharma (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2020)
Pedagogy for a teacher is very important because by mastering the pedagogy of the learning process carried out will get maximum results and in accordance with the objectives of carrying out the learning. This study aims to determine what factors a teacher should have so that in a learning process the teacher is able to create a good learning, appropriate teaching strategies and styles, as well as maximum knowledge and experience. The method used in this research is to use the literature study method, namely the data is collected using the literature study method. The data will be compiled, analyzed, and concluded to get a conclusion. Education in sports should be given to children from an early age such as formal education in schools. In the educational process, it cannot be separated from the role of a teacher in the classroom. The teacher's role is an application of pedagogy. Pedagogy of sports is a discipline of sports science that has the potential to integrate sub-disciplines of sports science to be able to underlie all practices in the field of sports that have the aim and purpose of being able to educate. Teachers must be able to have broad theoretical knowledge, apply in the classroom in using appropriate methods, and be able to manage the class so that the learning process can run well and achieve maximum results. Because, if the teacher only masters theories without the ability to manage the classroom using appropriate learning methods, the expectation of the desired results will not be achieved. So between theoretical knowledge and application of methods must be balanced in the learning process. All methods, media, references, and so on will be meaningless if a teacher is not able to perform their duties properly.